Molecular and cellular modulation of fibrinolysis - Kolev, Krasimir; Machovich, Raymund (Thrombosis and Haemostasis, 2003)
The structure of the fibrin network, the hemodynamic environment of the clot, the kinetic properties of the fibrinolytic enzymes and the balance of their formation and inactivation essentially determine the effectiveness of fibrinolysis in vivo. The fibrin structure and the action of proteases, however depend considerably on additional, apparently inert physiological and pathological factors, which are restricted to more or less transient compartments in fluid-solid interface, such as thrombus (fibrin with platelet membrane structures), endothelial cell surface, the environment of polymorphonuclear cells (PMN). In these compartments extreme changes in concentrations and rate enhancements are observed. Components released by endothelial cells, PMNs and platelets or molecules present in circulating blood create a heterogeneous milieu that modulates fibrinolysis. This review summarizes the effects, and where it is possible, explains the mechanism of modulators of the fibrinolytic processes, such as cell membrane and cellular contents of endothelium, PMN and platelets present in thrombi, the action of normal and pathological blood plasma- and extracellular matrix-components.
Keywords: Compartmental fibrinolysis; fibrin degradation; plasminogen activation; tPA-cofactors; endothelial cells; polymorphonuclear cells